REKOMENDASI KEBIJAKAN UNTUK PENGEMBANGAN PEKARANGAN PRODUKTIF DAN BERKELANJUTAN - Fadila, Aisyah Nur; Arifin, Hadi Susilo; Nurhayati, Nurhayati; Munandar, Aris (Pusat Studi Pembangunan Pertanian dan Pedesaan (PSP3) dan Ilmu Pengelolaan Sumberdaya Alam dan Lingkungan (PSL), 2024)
The potential of Metro Municipality's pekarangan contributes to food security, environmental sustainability, and community welfare in the post-Covid-19 era. Metro Municipality's pekarangan have a variety of plants that provide many benefits, including a source of fresh and healthy food for households. This research aims to raise awareness about the flexibility of pekarangan in adapting to changes, enabling them to withstand, recover from, and prepare for future disturbances. The typical size of a pekarangan, generally between 417 and 899 m2, provides an excellent opportunity to develop a complex agroforestry system. To fully realize this potential, policy recommendations include: 1) launching environmentally conscious education campaigns, 2) providing incentives and technical, 3) assistance integrating pekarangan management into urban development plans, and 4) establishing monitoring and evaluation systems for pekarangan. Maintaining the variety of plants found in 50% of the pekarangan is crucial. These plants include ornamental species (such as Aglaonema commutatum Schott, Sansevieria trifasciata Prain, Dieffenbachia seguine (Jacq.) Schott, and Adenium obesum (Forssk.) Roem. & Schult., fruit-bearing plants (like Carica papaya L., Musa paradisiaca L., and Persea americana Mill.), vegetables (including Capsicum frutescens L. and Allium fistulosum L.), and starch-producing plants (such as Manihot glaziovii Muell.Arg). The popularity of these plants is supported by the conducive growing environment in Metro Municipality.